Relationship Between Cultural Readiness and Social Adaptation of Manado State Polytechnic Students Abroad - Pantow, Vincentius; Wagiu, Decire D.; Mandang, Selvie R.I.; Longdong, Wingston M.J.; Wollah, Meidy (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to measure and analyze the relationship between cultural readiness (cultural knowledge, open-mindedness, and language proficiency) and the level of social adaptation of Manado State Polytechnic students who are studying or interning abroad. The research method used a correlational quantitative approach with a Likert scale-based questionnaire distributed to 30 respondents through purposive sampling. Data analysis included normality tests, Pearson's correlation, and simple linear regression. The results of the study show a significant positive correlation between cultural readiness and social adaptation (p < 0.05). Cultural knowledge and language skills have been proven to contribute significantly to students' ability to adapt socially. The cultural readiness training module that was developed and tested resulted in an average increase of 20% in cultural readiness and social adaptation scores. In addition, this study also provides policy recommendations for Polimdo's international program development unit to strengthen the pre-departure orientation of students.